Atezolizumab in invasive and metastatic urothelial carcinoma. Issue 12 (2nd December 2017) - Crist, Michael; Balar, Arjun
ABSTRACT: Introduction : Until recently, there has been little advancement in the management of invasive and metastatic urothelial cancer in over 30 years, and outcomes with cisplatin-based chemotherapy remain unchanged. Inhibitors targeting PD-1 signaling on cytotoxic T-cells have revolutionized bladder cancer therapy leading to durable responses. Atezolizumab is an engineered humanized anti-PD-L1 monoclonal antibody that inhibits PD-L1 binding to PD-1 and B7.1, enhancing immune-mediated tumor killing and is currently approved as second-line treatment after failure of platinum-based chemotherapy as well as first-line in cisplatin-ineligible patients. Areas covered : This article summarizes all reported phase I, II and III clinical trials that assessed the safety and efficacy of atezolizumab in the treatment of locally advanced and metastatic urothelial carcinoma. Expert commentary : Treatment with atezolizumab showed durable response and a toxicity profile that appears favorable to cytotoxic chemotherapy historically in the treatment of metastatic urothelial cancer among individuals who had progressed after prior platinum-based therapy and among those ineligible for treatment with first-line cisplatin. PD-L1 expression and tumor mutation load associate with response, however further research is needed to identify additional markers to improve prediction of response to atezolizumab.